2016
DOI: 10.1007/s00417-016-3538-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of orbital soft tissues on computed tomography to assess the activity of thyroid-associated orbitopathy

Abstract: The measurements of orbital soft tissue volume and density using CT scans can be used as a reliable and feasible technique to establish active inflammation in patients with TAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…The CAS is a valid score because there is correlation between pretreatment CAS and response to the immunomodulation. The CAS is useful for assessment of activity, but it is less useful for monitoring changes over time [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAS is a valid score because there is correlation between pretreatment CAS and response to the immunomodulation. The CAS is useful for assessment of activity, but it is less useful for monitoring changes over time [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies discuss the lacrimal gland involvement in thyroid eye disease. Computed to-mography and isotope study are used to assess lacrimal glands in patients with thyroid eye disease; however, they are associated with radiation exposure [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports described the utility of CT HU for the evaluation of soft tissues. Byun et al found a direct correlation between the in ammatory activity and the density of extraocular fat and lacrimal gland by using HUs in patients with thyroid-associated orbitopathy, and they concluded that the density could predict active in ammation [3]. Another report by Chikui et al revealed Lipoma had a speci c range of CT HU values and displaced the surrounding soft tissue [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, computed tomography (CT) scan is also one of the conventional modalities to assess knee OA. CT is excellent not only for depicting cortical bone and soft tissue calci cations [3], but also for the assessment of soft tissues [4]. It offers better visualization of subchondral bone cysts and osteophytes compared with MRI and radiography, and also helps surgical planning preoperatively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Volume or distribution changes of the soft tissue caused by orbital trauma and orbital relative diseases (such as orbital fracture, thyroid-associated ophthalmopathy (TAO), intraorbital tumor and so on) may lead to diplopia, restricted ocular movement and even impairment of visual function [3,4]. Precise assessment of intraorbital soft tissue is essential for diagnosis of intraorbital disorders, effect evaluation of treatment and planning for surgical intervention [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%